2011
DOI: 10.1186/1743-422x-8-271
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and phylogenetic analysis of small ruminant lentiviruses isolated from Canadian sheep and goats

Abstract: BackgroundSmall Ruminant Lentiviruses (SRLV) are widespread in Canadian sheep and goats and represent an important health issue in these animals. There is however no data about the genetic diversity of Caprine Arthritis Encephalitis Virus (CAEV) or Maedi Visna Virus (MVV) in this country.FindingsWe performed a molecular and phylogenetic analysis of sheep and goat lentiviruses from a small geographic area in Canada using long sequences from the gag region of 30 infected sheep and 36 infected goats originating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…There were 17 amino acid deletions in the Philippine CAEV isolate that could indicate that it is a new strain of the virus. In accordance with the study of L'Homme et al [31], the present study also showed that CAEV sequences isolated from goats contained a double glycine ''GG'' motif ( Fig. 1) that is characteristic of the CAEV-Cork lineage, and they were most similar to prototypical CAEV strains.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…There were 17 amino acid deletions in the Philippine CAEV isolate that could indicate that it is a new strain of the virus. In accordance with the study of L'Homme et al [31], the present study also showed that CAEV sequences isolated from goats contained a double glycine ''GG'' motif ( Fig. 1) that is characteristic of the CAEV-Cork lineage, and they were most similar to prototypical CAEV strains.…”
Section: Resultssupporting
confidence: 93%
“…The partial and complete coding sequences of the gag gene of CAEV from area 1 (Northern Philippines) and area 3 (Southern Philippines) ( Table 2) were successfully amplified using primers designed to detect proviral DNA of goats infected with caprine lentiviruses in the province of Quebec, Canada [31], and newly designed primers based on the CAEV Shanxi strain ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The members of this SRLV group in the Retroviridae family, maedi-visna virus (MVV) and caprine arthritis-encephalitis virus (CAEV), infect sheep and goats (L'Homme et al 2011). Small ruminant lentiviruses cause persistent infections which can induce systemic diseases affecting joints, mammary glands and respiratory and central nervous systems after long incubation periods (Narayan et al 1983).…”
mentioning
confidence: 99%
“…The gag and pol genes are relatively well conserved among SRLVs, which makes them ideal targets for Polymerase Chain Reaction (PCR) primer design (Pepin et al 1998;Grego et al 2007). The MVV prototypical strains such as strain K1514, EV-1, and SA-OMVV from sheep and the CAEV strain Cork-CAEV isolated from goat (L'Homme et al 2011) were originally viewed as distinct viral species restricted to respective host animal species. As more SRLV sequences had become available for phylogenetic analyses, it became evident that SRLVs can cross the species barrier and can be transmitted from sheep to goats under favourable conditions (Shah et al 2004b;Pisoni et al 2005).…”
mentioning
confidence: 99%
“…Furthermore, the three goats were finally confirmed for CAEV appearance in their blood by PCR technique according to a method described previously (17). The primers were designed corresponding to the most highly conserved sequences in the gag regions from available small ruminant lentivirus genomes in public databases to produce a 1327-bp amplicon.…”
Section: Goat Samplesmentioning
confidence: 99%